Along Navajo trails : recollections of a trader, 1898-1948 - Evans, Will, 1877-1954 (Utah State University Press, 2005)
Will Evans was the proprietor of the Shiprock Trading Company in early 20th century New Mexico. Probably more than most of his fellow traders, he had a strong interest in Navajo culture. He published in the local newspaper and other periodicals and compiled many of his pieces into a book manuscript. His subjects were Navajos he knew and traded with, their stories of historic events such as the Long Walk, and descriptions of their culture as he, an outsider without academic training, understood it.